Hiding in plain sight: observing planet-starspot crossings with the James Webb Space Telescope. Issue 4 (30th November 2021) - Bruno, Giovanni; Lewis, Nikole K; Valenti, Jeff A; Pagano, Isabella; Wilson, Tom J; Schlawin, Everett; Lothringer, Joshua; Lanza, Antonino F; Fraine, Jonathan; Scandariato, Gaetano; Micela, Giuseppina; Cracchiolo, Gianluca
ABSTRACT: Transiting exoplanets orbiting active stars frequently occult starspots and faculae on the visible stellar disc. Such occultations are often rejected from spectrophotometric transits, as it is assumed they do not contain relevant information for the study of exoplanet atmospheres. However, they can provide useful constraints to retrieve the temperature of active features and their effect on transmission spectra. We analyse the capabilities of the James Webb Space Telescope in the determination of the spectra of occulted starspots, despite its lack of optical wavelength instruments on board. Focusing on K and M spectral types, we simulate starspots with different temperatures and in different locations of the stellar disc, and find that starspot temperatures can be determined to within a few hundred kelvins using NIRSpec/Prism and the proposed NIRCam/F150W2+F322W2's broad wavelength capabilities. Our results are particularly promising in the case of K and M dwarfs of mag_K 12.5 with large temperature contrasts.